Why Atheism is more Natural than Religion - Szocik, Konrad (Studia religiologica, 2015)
Cognitive science of religion (CSR) suggests the naturalness of religion. Religious beliefs are viewed as natural because they are intuitive and cognitively effortless. They are also inevitable and more obvious than atheism. In consequence, atheism is an unnatural phenomenon which re-quires special cultural and social support. However, this naturalness of religion hypothesis seems overestimated. Here we show that atheism is more natural than religion and religious beliefs in the cognitive sense because it meets the criteria appropriate for natural selection in the sense of ultimate explanation. Religion and religious beliefs require cultural inputs. Without cultural support, they seem unnatural.